Autosomal-dominant osteopetrosis: An incidental finding - Rajathi Maria; Austin Ravi; Mathew Philips; Bharathi C; Srivastava Kumar (Wolters Kluwer Medknow Publications, 2010)
Osteopetrosis is a descriptive term that refers to a group of rare, heritable disorders of the skeleton. Osteopetrotic conditions vary greatly in their presentation and severity, from just as an incidental finding on radiographs to causing life-threatening complications such as bone marrow suppression. It is caused by failure of osteoclast development and function. Osteopetrosis can be inherited as autosomal-recessive, autosomal-dominant or as X-linked traits, with the most severe forms being the autosomal-recessive ones. The severity of the disease is mild to moderate in the autosomal-dominant forms, with normal life expectancy. Diagnosis is largely based on clinical and radiographic evaluation. The present paper reports a case of autosomal-dominant osteopetrosis complicated by osteomyelitis with a short review of the condition.